[PP.15.37] REDUCED RATE AND DURATION OF HYPERTENSION-RELATED HOSPITALIZATION AFTER TREATMENT WITH BAROREFLEX ACTIVATION THERAPY. (September 2017) - Halbach, M.; Grothaus, D.; Hoffmann, F.; Madershahian, N.; Kuhr, K.; Baldus, S.; Reuter, H.
Abstract : Objective: Baroreflex activation therapy (BAT) has been shown to lower blood pressure in patients with resistant hypertension. It is not known, however, whether this translates into a reduction of relevant clinical endpoints. Therefore, we investigated hospitalization rates before and after initiation of BAT. Design and method: After patients' written informed consent, records on hospitalization (dates of admission and discharge, main diagnosis) were obtained from medical insurance companies of 24 patients treated with the 2nd generation BAT system. Hospitalization data were annualized to account for variable periods of follow-up. Initial eligibility criteria for BAT were systolic office cuff blood pressure above 140 mmHg despite treatment with at least 3 antihypertensive drugs including at least one diuretic, and exclusion of secondary hypertension. Office cuff blood pressure was measured in sitting position with an automated system, which calculated the mean of 5 recordings at 2 min intervals. Data were tested for statistical significance by Wilcoxon test and are presented as mean ± standard deviation. Results: Records on hospitalization were available for a period of 1 year before BAT activation in 2 patients and 2 years before BAT activation in 22 patients. Follow-up after BAT activation was 1259 ± 498 days. The total number of hospitalizations was 3.3 ± 3.5 per year before BAT and 2.2 ± 2.7 per year after BAT (p = 0.03). Hospitalizations related to hypertension were significantly decreased from 1.5 ± 1.7 per year before BAT to 0.5 ± 0.9 per year after BAT (p < 0.01); scheduled hospitalization for BAT implantation was not counted. The cumulative duration of hypertension-related hospital stays was significantly reduced from 8.3 ± 9.1 days per year before BAT to 1.8 ± 4.8 days per year after BAT (p < 0.01). Office cuff blood pressure was 177 ± 26 over 99 ± 17 mmHg before BAT and 154 ± 32 over 90 ± 17 mmHg at latest follow-up (p < 0.01 for systolic and diastolic blood pressure). Conclusions: Besides the known reduction in blood pressure, BAT lowered the rate of hospitalizations related to hypertension in patients with severe resistant hypertension, suggesting that the positive effect of BAT on blood pressure may translate into a reduction of relevant clinical endpoints.